Rebate Decisions and Leadership Strategy in Competing Supply Chain with Heterogeneous Consumers. (26th December 2018) - Wang, Ziling; Mi, Jackson Jinhong; Liu, Bin
Abstract : Rebate is a traditional type of promotion, and it can benefit manufacturers and retailers with expanded demands. However, the impact of leadership strategy in rebate competition on supply chain members and rebate decision is still somewhat unclear. Our paper focuses on a horizontal competition with respect to both rebate and leadership between two manufacturers selling substitutable products through a common retailer to consumers who are heterogeneous in their price sensitivity. Furthermore, we investigate the impacts of leadership strategy on profits and study rebate decision under different strategies. Our research indicates that Bertrand-Nash game benefits the retailer, but hurts manufacturers, while Stackelberg game benefits manufacturers but hurts the retailer, which shows no difference from previous studies. In addition, the sequential-move Stackelberg game could eliminate the classic prisoners' dilemma in rebate decision, which is also influenced by fixed cost control.